2022
DOI: 10.3390/molecules27154800
|View full text |Cite
|
Sign up to set email alerts
|

Hesperidin Exhibits Protective Effects against PM2.5-Mediated Mitochondrial Damage, Cell Cycle Arrest, and Cellular Senescence in Human HaCaT Keratinocytes

Abstract: Particulate matter 2.5 (PM2.5) exposure can trigger adverse health outcomes in the human skin, such as skin aging, wrinkles, pigment spots, and atopic dermatitis. PM2.5 is associated with mitochondrial damage and the generation of reactive oxygen species (ROS). Hesperidin is a bioflavonoid that exhibits antioxidant and anti-inflammatory properties. This study aimed to determine the mechanism underlying the protective effect of hesperidin on human HaCaT keratinocytes against PM2.5-induced mitochondrial damage, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 48 publications
4
8
0
Order By: Relevance
“…These results indicated that ATX suppressed PM 2.5 -induced ROS generation through the activation of the NRF2-antioxidant enzyme pathways. PM 2.5 -induced oxidative stress causes DNA damage, which leads to cell cycle arrest in skin cells (26). The data of the present study revealed that ATX decreased base modification or breakage of DNA damage in PM 2.5 -treated cells Figure 6.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…These results indicated that ATX suppressed PM 2.5 -induced ROS generation through the activation of the NRF2-antioxidant enzyme pathways. PM 2.5 -induced oxidative stress causes DNA damage, which leads to cell cycle arrest in skin cells (26). The data of the present study revealed that ATX decreased base modification or breakage of DNA damage in PM 2.5 -treated cells Figure 6.…”
Section: Discussionsupporting
confidence: 49%
“…3D). A previous study revealed that PM 2.5 induces MMPs via the AP-1 signaling pathway through ROS generation (26). In addition, ROS increase the secretion of pro-inflammatory cytokines to high levels in most senescent cells (28).…”
Section: Discussionmentioning
confidence: 96%
“…4A ). Furthermore, evaluation of phospho-H2A.X, a marker for DNA double-strand breaks ( 25 ), showed that luteolin pretreatment diminished expression levels of phospho-H2A.X in H 2 O 2 -exposed cells ( Fig. 4B ).…”
Section: Resultsmentioning
confidence: 93%
“…Oxidative stress leads to DNA oxidation and mutation, cancer, and senescence [ 29 ]. PM 2.5 -induced oxidative stress causes DNA damage, which leads to cell cycle arrest in skin cells [ 44 ]. In this study, we noted less DNA damage in the 3-BDB and PM 2.5 groups than in the PM 2.5 group ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%